2023
DOI: 10.1186/s12883-022-03047-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of Glioblastoma patients with infratentorial recurrence

Abstract: Background Glioblastoma (GBM) infrequently recurs in the infratentorial region. Such Infratentorial recurrence (ITR) has some clinically unique characteristics, such as presenting unspecific symptoms and providing patients a chance to receive additional radiotherapy. However, the clinical significances of ITR are not well studied. Methods We reviewed newly diagnosed isocitrate dehydrogenase (IDH)-wildtype GBM patients treated at our institution bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Kawauchi et al reported a case series of cerebellar recurrence from supratentorial lesions and described that the recurrence might develop along the DRTC pathway [ 14 ]. In this study, we hypothesized that recurrence in the DN developed along the DRTC pathway based on the anatomical background of the DN.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kawauchi et al reported a case series of cerebellar recurrence from supratentorial lesions and described that the recurrence might develop along the DRTC pathway [ 14 ]. In this study, we hypothesized that recurrence in the DN developed along the DRTC pathway based on the anatomical background of the DN.…”
Section: Discussionmentioning
confidence: 99%
“…First, the predominant tumor location of the primary tumor was clarified. To the best of our knowledge, 10 cases of adult diffuse gliomas with recurrence in the DN have been reported in the literature [ 4 , 7 , 12 , 14 ]. Primary lesions in these cases were located at the frontal lobe in seven cases, thalamus in one case, and temporal lobe in one case [ 4 , 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations